Appraisal of Allostatic Load in Wild Boars Under a Controlled Environment - Nadia Piscopo; Anna Balestrieri; Nicola D’Alessio; Pasqualino Silvestre; Giovanna Bifulco; Alessio Cotticelli; Tanja Peric; Alberto Prandi; Danila d’Angelo; Francesco Napolitano; Luigi Esposito (Veterinary Sciences)
Besides metabolic and cardiovascular parameters, fluctuations in endocrine and inflammatory biomarkers might be regarded as reliable indicators of allostatic load. Among them, glucocorticoids have been shown to correlate with social stress in animals, regardless of whether they are dominant or subordinate, thus highlighting the crucial role of physiological energetic costs, together with social challenges, in the onset and severity of allostasis. Therefore, in the present work, we evaluated and monitored monthly the concentration of cortisol in bristles (pg/mg) over six months in young (n = 8), sub-adult (n = 5) and adult female wild boars (n = 5), which were kept in a controlled State Forest in Southern Italy. Our data revealed higher concentrations of cortisol in young animals when compared to sub-adult (p < 0.01) and adult (p < 0.05) groups. Moreover, such an increase faded away over time, and cortisol concentrations were found to be overlapping those of sub-adult and adult groups, which did not display any significant variation throughout monitoring. Collectively, our findings suggest that the wild boars adapted to the controlled environment, thus preserving both a physiological state and animal welfare.